Pengembangan Pembelajaran Pendidikan Agama Islam Anak Tunarungu: Kajian Kurikulum dan Hambatan Praktis - Hanipudin, Sarno; Rizqiyanti, Nurlaily (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2025)
This study explores the methods used in Islamic Religious Education (PAI) for deaf students, along with the supporting and inhibiting factors influencing the implementation of these methods at SLB Darussalam Karangpucung. Employing a qualitative approach with a phenomenological perspective, this research seeks to understand the lived experiences of educators and students within the inclusive learning environment. Data were collected through in-depth interviews, classroom observations, and document analysis. The data analysis process involved three stages: data reduction, data presentation, and conclusion drawing. The findings reveal that the PAI learning methods utilized include the lecture method, demonstration method, and habituation method. Teaching strategies are predominantly conventional, adopting a teacher-centered approach. The school implements an adapted version of the 2013 curriculum, aligned with the principles of the Independent Curriculum, and tailored to the needs and abilities of deaf students. Instruction is delivered using both sign language and spoken language to accommodate communication needs. Inhibiting factors identified include inadequate teacher competencies in special education, the unique characteristics of deaf students that require specialized approaches, and the unavailability of PAI textbooks specifically designed for deaf learners. On the other hand, supporting factors consist of a secure and inclusive school environment as well as active parental involvement in the educational process. These findings suggest the need for targeted teacher training and the development of inclusive instructional materials to enhance the quality of PAI learning for deaf students.